2008
DOI: 10.1109/tmi.2008.922187
|View full text |Cite
|
Sign up to set email alerts
|

Robust Linearized Image Reconstruction for Multifrequency EIT of the Breast

Abstract: Electrical impedance tomography (EIT) is a developing imaging modality that is beginning to show promise for detecting and characterizing tumors in the breast. At Rensselaer Polytechnic Institute, we have developed a combined EIT-tomosynthesis system that allows for the coregistered and simultaneous analysis of the breast using EIT and X-ray imaging. A significant challenge in EIT is the design of computationally efficient image reconstruction algorithms which are robust to various forms of model mismatch. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…We consider two choices of current patterns in our simulations. The first are the trigonometric patterns, (4) where denotes the total number of electrodes, , and is the current on the th electrode corresponding to the th current pattern. The second is the adjacent current pattern, a pairwise activation pattern otherwise.…”
Section: Measurement and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider two choices of current patterns in our simulations. The first are the trigonometric patterns, (4) where denotes the total number of electrodes, , and is the current on the th electrode corresponding to the th current pattern. The second is the adjacent current pattern, a pairwise activation pattern otherwise.…”
Section: Measurement and Simulationmentioning
confidence: 99%
“…Reconstruction algorithms for complex admittivities based on an iterative least-squares approach are found in [4], [15], [30] and an iterative package for 3-D reconstructions has been published in [42]. Another approach to the inverse problem is that of shape-based reconstruction methods for determining the location and shape of inclusions in the plane of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…We have validated this geometric approximation using saline-tank experiments with a specially constructed breast-shaped tank [25]. The application of currents on the electrodes of the top plane, where z = 0, induces a current density distribution at the top plane, denoted by j t and can be written as γU(x,y,0)z=jt(x,y). The superscript t implies the top plane, and b implies the bottom plane.…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
“…Tomographic EMI techniques generate an impedance (or conversely admittance) distribution map of the breast region, in which the presence of malignant lesions can be quantitatively assessed [3][4][5][19][20][21][22][23]. A recent study has shown that multi modality EMI approaches have an increased sensitivity and sensibility compared to individual EMI techniques [3].…”
Section: Introductionmentioning
confidence: 99%